O homem por trás da máscara: uma análise da metrossexualidade no discurso da indústria publicitária - Silva, João Paulo da (2012)
Since the middle of last century, the category of gender is no longer a sense of service to a policy of reproductive sex life in order to become the symbol of a crowd, serving to several possible theories. As a category that is based on the difference between the bodies, though traditionally these studies have been dedicated as a priority to women, the analysis of the male sphere becomes essencial for understanding the relational dynamics of the genre. Although contempt for the other side of the genre (explained by the historical context of enough tension within feminism), research on masculinity has become more frequent, because it has been realized that the relationships of domination also hurt the dominant actor. This inquiry continues in this direction and try to contribute to the deepening of studies of masculinity. Representations of masculinity are more diverse, so that during the process of writing this paper, we try to break the hegemonic model of male, showing that the forms of man have multiple variants, modifying itself according to social class, geographic region, race, religion, etc. Thus, in the world of social facts, one can speak of several men, not just one (as cultivates collective imagination). Among the archetypes produced man, this dissertation is dedicated to one in particular: the metrosexual. The representations of the male are undergoing significant transformations in the last two decades, especially with the rise of metrosexuality, a new male identity that is in dispute. It is noted, however, that the great forerunner of this new male image is advertising, since, being mass culture, this reflects ways of being extracted from society itself, encouraging them. So is the advertising discourse that materialize icons and signs which illustrate the formation of what is shaping up as a "new male profile". This inquiry is part of a survey that examines the representation of men in advertising, trying to observe how fragile is the talk of the metrosexual. Driving up, thus, a critique of consumption and new categories of gender.